IJAZ LUGHOWI PADA BAHASA AL-QUR’AN DALAMPANDANGAN IBNU ASYUR(TINJAUAN PADA KAJIAN ILMU BALAGHA) - Wahyu Apriandi Batubara; Lembayung Aurandyta; Harun Alrasyid (CV. Adiba Aisha Amira, 2024)
The purpose of this paper is to explore the aspects of i'jaz lughawi from the perspective of exegetes, especially through the study conducted by Ibn Ashur. I'jaz lughawi refers to the linguistic excellence embedded in Qur'ānic verses, which is considered proof of the Qur'ān's divinity. It involves an in-depth analysis of the Qur'ānic language structure, including word choice, syntax and rhetoric, and its impact on understanding and interpretation. In addition, the study also pays attention to the contribution of the study of balagha in understanding the richness of the Qur'anic language, especially in highlighting the beauty of language, rhetorical style, and the peculiarities of unique language structures. The research method used is qualitative-descriptive with a library analysis approach, in which Ibn Ashur to describe and analyze his views on lughawi i'jaz. The findings of this study are linguistic wonders (I'jaz Lughawi) in the Qur'an through the lens of Ibn Ashur's view. By combining the study of balaghah science with the interpretation of the Qur'an. With an in-depth analysis of how the beauty and wonder of the Qur'anic language is explained and understood through the principles of balaghah, which is associated with the interpretation of Ibn Ashur